Typology of Facade Building in Kayu Tangan Street corridor, Malang City - Piutanti, Resti (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
The Kayu Tangan Street Corridor is one of the areas that play an important role for Malang City. Building facade in this road corridor has significance in creating the visual character of Malang. The facade is an important architectural element of buildings because it can show the function and the significant meaning of the building. This study aims to determine how to classify the type of facade of the existing building in Street Corridor of Kayu Tangan that will affect the visual quality of this area. This study used a qualitative approach and descriptive-explorative methods. Selection of the sample was done by purposive sampling methods based on the buildings function. This study expected to gain a typology of building facade at Street Corridor of Kayu Tangan and led the development goal on the area to preserve the quality of its visual characterÂ DOI: https://doi.org/10.26905/lw.v11i2.2858